2019
DOI: 10.1186/s12893-019-0576-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Boerhaave’s syndrome: a case report with an intraoperative video

Abstract: Background Boerhaave’s syndrome involves a sudden elevation in the intraluminal pressure of the esophagus, causing a transmural perforation. It is associated with high morbidity and mortality. Its treatment is challenging, and early surgical intervention is the most crucial prognostic element. Case presentation We present a case of a 32 year-old male who presented after severe emesis with an acute onset of epigastric pain. He was diagnosed with Boerhaave’s syndrome. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
(22 reference statements)
0
14
0
6
Order By: Relevance
“…Two cases have required further thoracoscopic drainage and a pleural tap due to re-presentations with CT findings of a leftsided empyema and pleural effusion respectively. After which, symptoms resolved with targeted antibiotic and antifungal therapy based on pleural fluid analysis with no further re-interventions required [19,21]. Hence, we do suggest confirming that the pleural effusion if present pre-operatively is serous in nature prior to consideration for laparoscopic repair.…”
Section: Discussionmentioning
confidence: 52%
“…Two cases have required further thoracoscopic drainage and a pleural tap due to re-presentations with CT findings of a leftsided empyema and pleural effusion respectively. After which, symptoms resolved with targeted antibiotic and antifungal therapy based on pleural fluid analysis with no further re-interventions required [19,21]. Hence, we do suggest confirming that the pleural effusion if present pre-operatively is serous in nature prior to consideration for laparoscopic repair.…”
Section: Discussionmentioning
confidence: 52%
“…Which is the best way to approach BS is still a matter of debate: actual guidelines for thoracic esophageal perforation suggest an individualized approach to primary repair the tear, while for what concern specifically esophageal spontaneous rupture, most of the available studies considered the thoracotomy/thoracoscopic approach as the way of choice [9,[17][18][19][20][21]. Anyway, there is not any specific guidelines for BS: some case reports suggest that laparoscopy may be just as safe and effective [12,13]; lastly, some authors also reported conservative or endoscopic treatment: nevertheless, these are just a few studies involving patients with less severe clinical picture, so further researches are needed to better understand their feasibility in more challenging conditions [5,7]. In this case series, we present our 5 years' experience: in all patients, we choose to approach laparoscopically the esophageal tear; when necessary, afterwards we performed a thoracic lavage through left thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the type of surgical approach, thoracotomy is the most frequently chosen approach even if in literature there are several studies reporting transhiatal management as much as safe [11][12][13]. In our department, transabdominal approach is routinely adopted to treat BS.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous oesophageal rupture, also known as Boerhaave syndrome (BS), is a life-threatening benign disease of the gastrointestinal tract [3] that typically results from a sudden increase in intraoesophageal pressure such as forceful retching or severe vomiting [4] and most frequently occurs in the left wall of the lower third of the oesophagus, a site that is anatomically vulnerable [5]. BS, to our knowledge, has been demonstrated in various patients, including those with gastrointestinal stenosis, Barrett's oesophagus, ileus, and frequent vomiting during continued chemotherapy or gastroscopy and after general anaesthesia [3].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the literature indicate that the golden period for primary repair is the rst 24 hours of the event for oesophageal perforation when it can be associated with a 90% success rate [4]. The principles of treatment include removing the source of pollution, closing the breach, restoring the integrity of the oesophagus, full drainage, controlling the infection, strengthening nutritional support, improving the body and promoting wound healing [3,8].…”
Section: Discussionmentioning
confidence: 99%